Inventarisasi Serangga Entomofag yang Berasosiasi pada Bunga Pukul Delapan (Turnera ulmifolia) dan (Turnera subulata) di Perkebunan Kelapa Sawit (Elais guineensis Jacq.) PT. Dendy Marker Indah Lestari, Kabupaten Musi Rawas Utara, Sumatera Selatan - Shera Margaretha; Chandra Irsan (Universitas Merdeka Madiun, 2024)
Palm Oil Palm is a potential plantation to be developed in Indonesia. Pests are a limiting factor in oil palm cultivation factories. Pest attacks on oil palm plants can cause growth disturbances and defoliation of up to 100%. This study aims to determine the associated entomophage insects in T. subulata and T. ulmifolia plants. This research is a direct survey in the oil palm plantation of PT. Dendy Maker Indah Lestari, North Musi Rawas Regency, South Sumatra Province from September 2022 to November 2022. The results of the study found 11 entomophage insects associated with T. ulmifolia and T. subulata plants. These eleven insect species consist of 8 species of predatory insects belonging to 5 orders and 6 families there are Coccinella transversalis, Condylostylus sp., Syicanus croceovittatus, Syicanus croceovittatus, Cosmolestes picticeps, Rhynocoris rubricus, Odontomantis planiceps, Mantis religiosa, Citrine forktail and 3 species parasitoid insects belonging to 1 order and 2 families, there are Brachymeria sp., Antocephalus sp., and Aleiodes sp. The most dominant predatory insect species found was C. picticeps with a total of 441 individuals. The most dominant parasitoid insect species found was Brachymeria with a total of 3108 individuals. The conclusion in this study was that more dominant predatory insect species were found associated with flowers than parasitoid insects.